If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 28 = 6x + -15 Reorder the terms: 28 + 4x = 6x + -15 Reorder the terms: 28 + 4x = -15 + 6x Solving 28 + 4x = -15 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 28 + 4x + -6x = -15 + 6x + -6x Combine like terms: 4x + -6x = -2x 28 + -2x = -15 + 6x + -6x Combine like terms: 6x + -6x = 0 28 + -2x = -15 + 0 28 + -2x = -15 Add '-28' to each side of the equation. 28 + -28 + -2x = -15 + -28 Combine like terms: 28 + -28 = 0 0 + -2x = -15 + -28 -2x = -15 + -28 Combine like terms: -15 + -28 = -43 -2x = -43 Divide each side by '-2'. x = 21.5 Simplifying x = 21.5
| -4(a+3)-7= | | 114=-2x-8+5x | | 0=5-5y+7x | | 14x^2-46x+12=0 | | 4n+1=4n+1 | | 4x+6-7x+9=18 | | 6-(2n+3)-4n=6 | | 2x=5x-30 | | 12z-1=z^2+35 | | (x-9)+(.5x)=180 | | -3=3w-(4w+6) | | y^2+12y+20= | | 6=2(x+8)-5y | | 7x-8y=16 | | m^2+13m+40=0 | | 4x+5=11-3x | | -10x+3=5x-2 | | 3x-22= | | 2x-22= | | 3x-34= | | 3x^2-6x+2k=0 | | 3x=(x+1)(x+2)+8 | | 4(6+2x)=0 | | x+15=2(x-10) | | x+15=2(x-15) | | 8w-11=-8w | | 3x=11+1 | | -7x-10=-3x-14 | | 2x+2y=22 | | 8w+40=0 | | 3x+1y=20 | | 11.6b+2=3.8b+38.66 |